Assessment and Simulation of Impacts of Climate Change on Erosion and Water Flow by Using the Soil and Water Assessment Tool and GIS: Case Study in Upper Cau River basin in Vietnam - Thai, Tran Hong; Thao, Nguyen Phuong; Dieu, Bui Tien (Vietnam Journal of Earth Sciences, 2017)
The Upper Cau river basin which plays an important role in socio-economic developments the North of Vietnam is sensitive to changes of climate influencing flows, erosion, and water resources. The main objective of this study is to assess and simulate impacts of climate change on erosion and water flow in the basin. Using a GIS database and Soil and Water Assessment Tool (SWAT) model, the water flow and soil loss were assessed with data in period 1980-1999 called the based period, then simulated until 2100 considering the medium emission scenario (B2). The simulation result showed that the total annual runoff and soil loss tends to increase compared to the base period. For flow, the change rate of the simulation period is higher than the base period; the water flow rate will increase by 0.22% (2020-2039) and up to 1.37% (2080-2100). The total annual soil loss of the simulation period at Gia Bay station tends to increase steadily compared to the baseline, namely by 6.2% (2020-2039) and 25.5% (2080-2100). Overall, the result in this study shows that effects of climate changes on the basin are severe enough under the scenario B2 which is useful for authorities for basin management. References Ali R., McFarlane D., Varma S., Dawes W., Emelyanova I., Hodgson G., Charles S., 2012. Potential climate change impacts on groundwater resources of south-western Australia. Journal of Hydrology, 475, 456-472. doi: http://dx.doi.org/10.1016/j.jhydrol.2012.04.043 Arnell N. W., 2004. Climate change and global water resources: SRES emissions and socio-economic scenarios. Global Environmental Change, 14(1), 31- 52. doi:10.1016/j.gloenvcha.2003.10.006 Arnold J. G., Fohrer N., 2005. SWAT2000: Current capabilities and research opportunities in applied watershed modeling. Hydrol. Proc., 19(3), 563-572. Arnold J.G., Kiniry J.R., Srinivasan R., Williams J.R., Haney E.B., Neitsch S.L., 2012. Soil and water assessment tool. Input/output Documentation: Texas Water Resources Institute. Beare S., Heaney A., 2002. Climate Change and water resources in the Murray Darling Basin, Australia, impacts and possible adaptation. Paper presented at the World Congress of Environmental and Resource Economists, Monterey, California, USA. Binh N.D., Tuan N.A., Huong H.L., 2010. SWAT application coupled with web technologies for soil erosion assessment in north western region of Vietnam. Paper presented at the International SWAT Conference Mayfield Hotel. Seoul, South Korea: Hanoi University of Algriculture. Chau T.L.M., Tuan N.Q., 2011. Application of SWAT for soil erosion management at river subbasins in Duong Hoa commune, Huong Thuy town, Thua Thien Hue province. Paper presented at the 3rd National GIS conference Danang University of Education, Danang, Vietnam. CLIMsystems. http://www.climsystems.com/simclim/. Department of Geography, L. U. SDSM Statistical Downscaling Model: http://copublic.lboro.ac.uk/cocwd/SDSM/software.html. FAO. http://www.fao.org/land-water/databases-and-software/cropwat/en/. Hanratty M.P., Stefan H.G., 1998. Simulating climate change effects in a Minnesota agricultural watershed. J. Environ. Qual., 27, 1524-1532. IPCC, 2000. Special Report on Emissions Scenarios. United States of America. IPCC, 2007. Fourth Assessment Report: Climate Change 2007 (AR4). Li Y., Chen B.M., Wang Z.G., Peng S.L., 2011. Effects of temperature change on water discharge, and sediment and nutrient loading in the lower Pearl River basin based on SWAT modeling. Hydrolog. Sci. J., 56, 68-83. Liem N.D., Hong N.T., Minh T.P., Loi N.K., 2011. Assessing water discharge in Be river basin, Vietnam using GIS and SWAT model. Paper presented at the National GIS application Vietnam. http://gisnetwork.vn/wpcontent/uploads/2012/04/GIS2011_BAI1.swf. McBean E., Motiee H., 2008. Assessment of impact of climate change on water resources: a long term analysis of the Great Lakes of North America. Hydrology and Earth System Sciences, 12, 239-255. MONRE, 2009. Climate Change, Sea level rise scenarios for Vietnam. Vietnam. MONRE, 2012. Climate Change, Sea level rise scenarios for Vietnam. Vietnam. MONRE, 2016. Climate Change, Sea level rise scenarios for Vietnam. Vietnam. Nhu N.Y., 2011. Researching on the impacts of Climate Change on the extreme of the flow on Nhue-Day rivers basin, Hanoi. (Master), Hanoi University of Science, Hanoi National University, Vietnam. Ouyang W., Gao X., Hao Z., Liu H., Shi Y., Hao F., 2017. Farmland shift due to climate warming and impacts on temporal-spatial distributions of water resources in a middle-high latitude agricultural watershed. Journal of Hydrology, 547, 156-167. http://dx.doi.org/10.1016/j.jhydrol.2017.01.050 Phan D.B., Wu C.C., Hsieh S.C., 2011. Impact of Climate Change and Deforestation on Stream Discharge and Sediment Yield in Phu Luong Watershed, Viet Nam Environmental Science and Engineering, 5, 1063-1072. Phan D.B., Wu C.C., Hsieh S.C., 2011. Impact of Climate Change on Stream Discharge and Sediment Yield in Northern Vietnam. Water Resources, 38(6), 827-836. doi: 10.1134/S0097807811060133. Rossi C.G., Srinivasan R., Jirayoot K., Duc T.L., Souvannabouth P., Binh N.D., Gassman P.W., 2009. Hydrologic evaluation of the lower Mekong river basin with the soil and water assessment tool model. International Agricultural Engineering, 18, 1-13. Son N.T., Tuan N.C., Hang V.T., Nhu N.Y., 2011. Impact of climate change on water resources to transform Nhue-Day rivers basin. Natural and Technological Science, 27, 218-226. Thang T.Q., 2010. Application of remote sensing images and GIS technique to assess soil erosion in Tam Nong Commune, Phu Tho province. Master. Hanoi University of Agriculture, Hanoi. Trong T.D., Viet N.Q., Huong D.T.V., 2012. Assessing the soil erosion possibility in Dakrong Commune, Quang Tri province using RMMF (Rrevised Morgan-Morgan-Finney) model. Scientific journal, Hue University,Vietnam, 74A(5), 173-184. Tu L.H., Liem N.D., Minh T.P., Loi N.K., 2011. Assessing soil erosion in Da Tam watershed, Lam Dong province using GIS technique Paper presented at the National GIS application Danang, Vietnam. Penginapan Ciawi. (2020). Retrieved 21 May 2020, from http://www.penginapanciawi.my.id/ Vargas-Amelin E., Pindado P., 2014. The challenge of climate change in Spain: Water resources, agriculture and land. Journal of Hydrology, 518, Part B, 243-249. http://dx.doi.org/10.1016/j.jhydrol.2013.11.035 Winchell M., Srinivasan R., Di Luzio M., Arnold J., 2013. ArcSWAT Interface for SWAT 2012. User’s Guide. Texas: Blackland Research and Extension Center; Grassland Soil and Water research laboratory.